2006
DOI: 10.2459/01.jcm.0000237914.12915.dd
|View full text |Cite
|
Sign up to set email alerts
|

Severe ventricular dysrhythmias and silent ischemia during infusion of the antimetabolite 5-fluorouracil and cis-platin

Abstract: The antimetabolite 5-fluorouracil is frequently used in the therapy of various malignancies. Cardiotoxicity has frequently been described during treatment, but there is no common agreement on the need to perform cardiovascular monitoring of patients during 5-fluorouracil administration. We report the case of a young patient with an head-neck cancer on whom a continuous electrocardiogram recording was performed, documenting serious ventricular dysrhythmias in the presence of myocardial ischemia during 5-fluorou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 22 publications
0
20
0
1
Order By: Relevance
“…Chronic anthracycline cardiotoxicity (even many years after the completion of therapy) manifests often as life-threatening arrhythmias [34]. 5-Fluorouracil has been demonstrated to be associated with EKG signs of myocardial ischemia while less frequent alterations include arrhythmias [35]. High dose of cyclophosphamide may cause malignant arrhythmias inducing sometimes fatal outcomes [36].…”
Section: Ekg and Cardiotoxicity Of Ctmentioning
confidence: 99%
“…Chronic anthracycline cardiotoxicity (even many years after the completion of therapy) manifests often as life-threatening arrhythmias [34]. 5-Fluorouracil has been demonstrated to be associated with EKG signs of myocardial ischemia while less frequent alterations include arrhythmias [35]. High dose of cyclophosphamide may cause malignant arrhythmias inducing sometimes fatal outcomes [36].…”
Section: Ekg and Cardiotoxicity Of Ctmentioning
confidence: 99%
“…A major factor limiting cisplatin treatment is concern regarding its acute and cumulative cardiotoxicity 7,8 . Clinical reports regarding acute cisplatin treatment have identified myocardial infarction and severe ventricular arrhythmias in young patients 9,10 . Those studies suggested that the use of cisplatin can be a risk factor for coronary heart disease.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to increasing the frequency of cardiotoxicity, the presence of preexisting heart disease increases the severity of cardiotoxic reactions to 5-FU [3]. Accordingly, a careful pre-administration cardiac evaluation is essential [46].…”
Section: Risk Stratificationmentioning
confidence: 99%
“…Thus, in conjunction with a thorough pre-treatment clinical assessment, frequent symptom, blood pressure, and ECG monitoring are essential components of any treatment protocol [46].…”
Section: Risk Stratificationmentioning
confidence: 99%